PENGARUH KEGIATAN PAPERCRAFT TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK LABOR FKIP UNIVERSITAS RIAU - Elsa Muharnalis; Ria Novianti; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the results of field observations of the fine motor skills of the students have not developed optimally. So that should be the implementation of activities papercraft. This study aims to determine the effect of papercraft activities against the fine motor skills of children aged 5-6 years in kindergarten Labor FKIP Riau University. The sample used in this study 23 people protégé. The data collection techniques were used that observation and documentation. Data were analyzed using t-test using SPSS 20.0. The research hypothesis is papercraft activities have an influence on the fine motor skills 5-6 years old in kindergarten Labor FKIP Riau University. It can be seen from the analysis of data obtained by t = 17 683 and Sig. (2-tailed) = 0.000. because Sig. (2-tailed) = 0.000 <0, 05, it can be concluded that there is a subtle difference in the ability of Motor significant protégé after papercraft in learning activities. So it means Ho rejected and Ha accepted which means there is a very significant difference between before and after the experiment by applying papercraft activities. Papercraft activity influence on the fine motor skills of children aged 5-6 years in kindergarten Labor FKIP University of Riau, amounting to 43.09%.Keywords: Fine Motor Ability, Activity Papercraft